(3GdJLGQI GdGdcJQhfjI (B/s - (3HSjhfj, YHO GdMejOs ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ h GdJhRjY(B, s, 2003)
(3JLO aj gPG GdcJGH (B: (3THcI GdCfJQfjJ hGdJLGQI GdEdcJQhfjI ,GdJLGQI GdJbdjOjI hJLGQI THcI GdhjH , JLGQI GdCYeGd hGdMcheI GdEdcJQhfjI ,CNWGQ hJgOjOGJ JCejf GdJLGQI GdEdcJQhfjI , JTajQ GdHjGfGJ , fXe GdOaY hGdSOGO hGdfbhO GdEdcJQhfjI ,EbGeI JLGQI EdcJQhfjI, GdHfjI GdJMJjI hGdJCejf hJNWjW GdCef ,JVNje hEYOGO NOeGJ hehGbY GdJLGQI GdEdcJQhfjI(B.s
Keywords: (3GdCfJQfJs; (3GdJLGQIs; (3GdJLGQI GdEdcJQhfjIs